درجة الالتزام بمعيار التدقيق الجزائري ( 530 ) "السبر في التدقيق" في الجزائر (دراسة حالة عينة من مهني المحاسبة: The degree of compliance with the Algerian auditing standard (530) “sounding in auditing” in Algeria (a sample case study of an accountancy professional) - لصنوني حفيظة (Journal of North African Economies, 2025)
This study aims to identify the extent to which audit offices in Algeria use the requirements of the Algerian auditing standard “sounding in auditing”, related to the use of samples in auditing in order to reach the best audit evidence and improve the quality of auditing in Algeria. Certified account keepers and accountants, in addition to a group of specialized university professors. The study used a set of statistical methods to reach the results of the study, including descriptive statistics, and the study showed that audit offices in Algeria are committed to applying the requirements of the local auditing standard. Similar to the characteristics of the community from which it was taken, and the auditor’s use of his professional judgment and experience so that he can determine the acceptable level of errors in order to determine an acceptable sample size, and the auditor should be careful when evaluating the results of the sampling audit process so that sufficient and appropriate evidence can be obtained.